LABOUR PRODUCTIVITY OF DAIRY CATTLE FARMING IN CENTRAL AND SOUTHEAST BULGARIA - K. Stankov (Trakia Journal of Sciences)
A study was conducted on labour productivity in dairy cattle farms that breed Black-and-White cows. The study encompassed 90 farms, thus including 6471 cows. The farms were divided into four groups: small – 8 farms with an average of 3.6 cows; medium – 32 farms with an average of 22.9 cows; large – 32 farms with an average of 74.2 cows; and huge – 18 farms with 185.3 cows per farms. The results of the study indicated that large and huge farms are distinguished by high labour productivity. The income from production, profit, milk quantities, and the cost of one annual work unit (AWU) and a man-hour were several times higher compared to small and medium farms. Production was organised at a much better technological level, which was a contributing factor towards high-quality and competitive milk production. A recommendation to the small and medium farms would be to grow larger, improve their selection, and develop technologically.